Body weight and body conformation of Cyprus Shami and Boer goats in Malaysia - Mohamed Hadi, Hamdan (2011)
Thirty Boer and 30 Cyprus Shami goats were measured for their body weights, height at withers, body length and heart girth. Each breed was divided into three age groups: group 1 (6-12 months old), group 2 (12-18 months old) and group 3 (more than 18 months old). Means for linear body measurements according to age groups were compared between Shami and Boer goats. There was a highly significant differences (p<0.005) between Boer and Cyprus Shami goats in term of each body measurement and body weight. In the present study, to predict the body weight of Cyprus Shami goat, the combination of three parameters of linear body conformation can be used.